Monitoring Fruit Fly Species in Pumpkin Field and Detection of Melon Fruit Fly Zeugodacus cucurbitae from Infested Cucumber Fruits - sigdel, Deepa; Adhikari, Debraj; Adhikari, S; Dhungana, A; Acharya, Rabin (Andalasian International Journal of Entomology, 2025)
Numerous fruit fly species pose enormous threats to fruit and vegetable production worldwide, resulting in both quantitative and qualitative losses. The experiment evaluated the effectiveness of five different traps in a pumpkin (Cucurbita pepo) field located in Mahalaxmi municipality-6, Lalitpur district, Nepal, from April to June 2024. Yellow sticky trap, plastic bottle trap, bucket trap, steiner trap and plastic glass trap were used as treatments, provided with a cotton wick soaked in 0.5 ml of cue lure (except yellow sticky trap) placed at 1 m height on a standing stick in the pumpkin field. Throughout the collection, Zeugodacus cucurbitae was the most abundant, with a total of 1300 flies, followed by Zeugodacus tau, Bactrocera dorsalis, and Bactrocera nigrotibialis, respectively. In total, the highest average capture was led by the steiner trap, followed by the bucket trap, while the yellow sticky trap was the least effective. Laboratory rearing of fruit flies resulted in the emergence of a single species, Zeugodacus cucurbitae. Average pupal size was 5.67 ± 0.052 mm length, 2.15 ± 0.041 mm breadth, and weighed 14.90 ± 0.31 mg. Female adults were larger than males, measuring 7.59 ± 0.18 mm body length and 14.76 ± 0.31 mm wingspan, compared to males (6.98 ± 0.12 mm length and 14.65 ± 0.24 mm wingspan), and the ovipositor measured 1.75 ± 0.056 mm. This indicates a single species oviposits in a single fruit.